Compendium of success stories in integrated soil fertility management. Farmer’s voices from Babati District in Tanzania - Kihara, Job Maguta; Kinyua, Michael; Massam, Jonus; Pallagjo, Rose; Songoyani, Inot; Kyekaka, Jetrida (2022)
The compendium brings together success stories told by farmers, the beneficiaries of the Africa RISING ESA project. It describes how the integrated sustainable agriculture systems transformed the lives of many small-scale farming households living in Babati district, Tanzania. It also highlights demand-driven technologies introduced to farmers to address the top-line challenges facing a vast majority of small-scale farmers in this area. It further provides evidence of the success of adopting the appropriate farming technologies. In a review of the most promising sustainable intensification farming technologies suitable for Babati, it was clear that the Mbili Mbili strip cropping, ISFM-Integrated soil fertility management practices such as planting in appropriate space, and the use of improved seed varieties and manure application provide potential benefits to farmers. Thanks to the Africa RISING project. To bridge the yield gaps, fight pests and diseases attacking small-scale farming households’ produce, and create enabling market conditions for farmers, the Africa RISING Project has been supporting action research to address these top-line challenges. Together with the research and development partnership, the project empowers farmers with sustainable intensification options. These options benefit small-scale farmers with improved productivity, better income, nutrition, and food safety.